Control of parasitic infections among school children in the peri-urban area of Botucatu, São Paulo, Brazil - Regina Coeli Cunha Dórea; Ednir Salata; Carlos Roberto Padovani; Gilberto Lupi dos Anjos (Revista da Sociedade Brasileira de Medicina Tropical, 1996)
Tide prevalence of intestinal parasitosis ivas investigated in a primaiy school located in Rubiâo Júnior, a peri-urban district of Botucatu, São Paulo slate, Brazil, in order to assess the effect of treatment and practical measures of prophylaxis in the control of parasitic infections among 7-to- 18-year-old school children of a low socio-economic status. The first series of parasitological examinations included 219 school children, ef which 123 (56.1 %) were found to be infected with one or more parasite species. Eighty- four children canying pathogenic parasites were submitted to various anti-parasitic treatment schedules. We re-evaluated 15 (89 %) students after 4 to 6 months post- chemotherapy. The results indicate that the combination of treatment with prophylactic measures has been successful in the control of parasitic infections, since reinfection rates were generally low (< 5-3 %), except for Giardia lamblia infections (18.6 %), and a marked reduction oti the prevalence rates was obsewed with a significant percentage of cure (> 73-1 %) in children infected with most parasite species. The reasons for the apparent failure in the control of infections caused by Hymenolepis nana and Strongyloides stercoralis are discussed.